1993
DOI: 10.3758/bf03334931
|View full text |Cite
|
Sign up to set email alerts
|

Ordinal measurement of autistic behavior: A preliminary report

Abstract: Ordinal diagnostic criteria were developed and used to assess the clinical characteristics of 20 autistic children. Subgroups of autistic children were identified and, on the basis of rankings on behavioral measures and performance on standardized tests and indices of school achievement, found to differ with respect to general level of functioning and educational placement. Developmental changes, expected in autistic children over a 12•year period, were reflected in higher rankings, especially for those in les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This is one of the main goals of Crawley's research team which is in the process of designing a set of tasks with face validity for the defining features of autism: deficits in appropriate reciprocal social interactions, deficits in social communication, and high levels of ritualistic repetitive behaviors (Crawley 2004). As underlined by Fisch (2005), some studies using factor or cluster analyses suggest also that three dimensions (cognitive abilities, social function and restrictive interest or activities) are necessary in the assessment and conceptualization of autism (Dihoff et al 1993;Szatmari et al 2002).…”
Section: Similarity Of Observable Behaviorsmentioning
confidence: 98%
“…This is one of the main goals of Crawley's research team which is in the process of designing a set of tasks with face validity for the defining features of autism: deficits in appropriate reciprocal social interactions, deficits in social communication, and high levels of ritualistic repetitive behaviors (Crawley 2004). As underlined by Fisch (2005), some studies using factor or cluster analyses suggest also that three dimensions (cognitive abilities, social function and restrictive interest or activities) are necessary in the assessment and conceptualization of autism (Dihoff et al 1993;Szatmari et al 2002).…”
Section: Similarity Of Observable Behaviorsmentioning
confidence: 98%
“…Therefore, one should not be surprised to find that a single component falls out from the factor analysis. On the other hand, when Dihoff et al [1993] employed six ordinal scales by which to assess autism and performed a cluster analysis, they found that two distinct dimensions emerged: (1) general problem-solving ability; and (2) general social awareness. Szatmari et al [2002] used scores from the VABS and ADI and performed a factor-analytic procedure, from which two dimensions of autism also emerged.…”
Section: Webster's Third International Dictionarymentioning
confidence: 99%
“…Therefore, one should not be surprised to find that a single component falls out from the factor analysis. On the other hand, when Dihoff et al [1993] employed six ordinal scales by which to assess autism and performed a cluster analysis, they found that two distinct dimensions emerged: (1) general problem‐solving ability; and (2) general social awareness. Szatmari et al [2002] used scores from the VABS and ADI and performed a factor‐analytic procedure, from which two dimensions of autism also emerged.…”
mentioning
confidence: 99%